1996
DOI: 10.1093/ije/25.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Neoplasia in Pap Smears: Risk of Cervical Intra-Epithelial Neoplasia (CIN) after Negative or No Prior Smears in a Population without a Mass Screening Programme

Abstract: Stalsberg H. Cervical neoplasia in Pap smears. Risk of cervical intra-epithelial neoplasia (CIN) after negative or no prior smears in a population without a mass screening programme International Journal of Epidemiology 1996; 25: 53-58. Background. The aim of this study was to examine, In a population not submitted to mass screening, the risk of cancer and cervical intra-epithelial neoplasia (CIN) in Pap smears from women without previously reported positive smears. Methods. In a logistic regression model cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…The CIN3 rate at entry in women with no previous smear history was similar to that in the screened population both in our cohort (Table 1) and in a Norwegian study (Forsmo et al, 1996), and the rate at their second smear was slightly less than in previously screened women (Table 4). A much lower CIN3 rate was observed at the second smear than at entry in a national study of inadequately screened low-income American women (Sawaya et al, 2003), but this may reflect confounding between screening interval and number of negative smears.…”
Section: Cytological Regression Of Cin3supporting
confidence: 82%
“…The CIN3 rate at entry in women with no previous smear history was similar to that in the screened population both in our cohort (Table 1) and in a Norwegian study (Forsmo et al, 1996), and the rate at their second smear was slightly less than in previously screened women (Table 4). A much lower CIN3 rate was observed at the second smear than at entry in a national study of inadequately screened low-income American women (Sawaya et al, 2003), but this may reflect confounding between screening interval and number of negative smears.…”
Section: Cytological Regression Of Cin3supporting
confidence: 82%
“…However, the finding that women with lesions progressing to tissue-proven CIN 3 were younger at CIN debut than those with regressing lesions is in keeping with earlier reports [5,17,18,21]. It fits in with the fact that CIN 1-2 has maximum frequency among women in their twenties, while CIN 3 peaks in those aged 35-39 years [6,7]. This would be compatible with a stepwise development of CIN.…”
Section: Discussionsupporting
confidence: 90%
“…These lesions often run a fluctuating course and may even regress [4,5]. While it is widely accepted that women in their twenties are at high risk of developing CIN [6,7], the situation in women who have provided a series of negative smears and thus represent an older age group, has received less attention. These women have increased relative protection against cervical cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…The results on smear history were unrepresentative, as the majority of this birth cohort had not accumulated three consecutive regular smears. An audit of the screened population in the UK found that only 21% of women aged 50 would be eligible for early withdrawal on the basis of an adequate smear history (15) . This reflects the comparatively recent introduction of systematic call/recall in the UK since 1988.…”
Section: Discussionmentioning
confidence: 99%